Stella-Cre Mice are Highly Efficient Cre Deleters - Liu, Hui (Wiley Subscription Services, Inc., A Wiley Company, 2011)
Cre-loxP recombination is widely used for genetic manipulation of the mouse genome. Here, we report generation and characterization of a new Cre line, Stella-Cre, where Cre expression cassette was targeted to the 3′ UTR of the Stella locus. Stella is specifically expressed in preimplantation embryos and in the germline. Cre-loxP recombination efficiency in Stella-Cre mice was investigated at several genomic loci including Rosa26, Jak2, and Npm1. At all the loci examined, we observed 100% Cre-loxP recombination efficiency in the embryos and in the germline. Thus, Stella-Cre mice serve as a very efficient deleter line. genesis 49:689–695, 2011. © 2011 Wiley-Liss, Inc.